2014
DOI: 10.1186/1471-2105-15-217
|View full text |Cite
|
Sign up to set email alerts
|

A semi-local neighborhood-based framework for probabilistic cell lineage tracing

Abstract: BackgroundAdvances in fluorescence labeling and imaging have made it possible to acquire in vivo records of complex biological processes. Analysis has lagged behind acquisition in part because of the difficulty and computational expense of accurate cell tracking. In vivo analysis requires, at minimum, tracking hundreds of cells over hundreds of time points in complex three dimensional environments. We address this challenge with a computational framework capable of efficiently and accurately tracing entire cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 24 publications
(26 reference statements)
0
49
0
Order By: Relevance
“…We found that 41% of the time the phenotypes were penetrant at the cellular level (Figure 1H). To ensure correct of lineage tracing, we performed multiple rounds of manual curation on the automatically generated lineages (Santella et al, 2014) (Figures S2D and Extended Experimental Procedures). Based on human examination of 100 randomly picked cell tracks post curation, we found that 96% of terminal cells were correctly traced (Figure 1I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that 41% of the time the phenotypes were penetrant at the cellular level (Figure 1H). To ensure correct of lineage tracing, we performed multiple rounds of manual curation on the automatically generated lineages (Santella et al, 2014) (Figures S2D and Extended Experimental Procedures). Based on human examination of 100 randomly picked cell tracks post curation, we found that 96% of terminal cells were correctly traced (Figure 1I).…”
Section: Resultsmentioning
confidence: 99%
“…3D, time-lapse imaging now allows in toto imaging of metazoan embryogenesis in different model organisms and tracking of individual cells (Bao et al, 2006; Keller et al, 2008; McMahon et al, 2008; Udan et al, 2014; Wu et al, 2013; Xiong et al, 2013). In C. elegans , it allows direct tracing of the whole cell lineage (Bao et al, 2006; Santella et al, 2014; Santella et al, 2010). By combining automated lineaging with tissue-maker expression-based assessment of cell types, we have recently shown that progenitor cell fates can be systematically assayed (Du et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These efforts generated an integrated suite of methods and tools that dramatically increased efficiency in lineage tracing and allowed new applications. After collecting 4D fluorescent images using a wide variety of microscopy platforms (Bao et al ., ; Moore et al ., ; Murray and Bao, ; Richards et al ., ; Wu et al ., ), the analysis software StarryNite identifies (Santella et al ., ), and tracks (Santella et al ., ) nuclei over time. The automated process is highly accurate (>99.6%) but the sheer number of cells being identified and tracked requires manual curation and editing of the automated output, which is facilitated by custom software (AceTree)(Boyle et al ., ).…”
Section: Methods For Lineage Analysis In Embryosmentioning
confidence: 99%
“…Indeed, recent improvements in computer algorithms now allow real-time nuclear tracking in C. elegans embryos5051. Thus a complete description of C. elegans nervous system assembly on a cell-by-cell basis should be feasible.…”
Section: Discussionmentioning
confidence: 99%